Perencanaan dan Peracangan Fasilitas Resort Ramah Lansia di Ubud, Gianyar, Bali - Singantara, Made Benyco; Parwata, I Wayan; Gunawarman, A.A. Gede Raka (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Planning and Design of Facilities for an Elderly Friendly Resort in Ubud, Gianyar, Bali, is an overnight tourist accommodation aimed at the elderly who want to stay with a sense of security and have a natural natural feel in this Elderly Friendly Resort Facility. There are several supporting facilities at this Elderly Friendly Resort ranging from physical and spiritual activities for the elderly such as tennis, golf, gym, meditation. This Elderly Friendly Resort is located in Ubud Village, where Ubud Village is a tourism area in Bali which has several tourist accommodation places. The methods used in the Planning and Design of Elderly Friendly Resort Facilities are data collection methods, data compilation methods and discussion methods. The village that will be used as the site for Planning and Designing this Elderly Friendly Resort is in Ubud Village, which is located on Jalan Suweta, north of Ubud village, because around Jalan Suweta ubud it still has an unspoiled natural atmosphere in the form of rice fields and there is vegetation. lush and close to several tourist accommodations in Ubud Village. The function of this elderly-friendly resort facility is as a place to stay for the elderly who are traveling around the Ubud Village. By using the Anthropometric Architectural Approach, with the Basic Concept applied namely "Nature and Comfort" and using the Basic Theme, namely Traditional Tropical Architecture where the application of the Basic Concept and Basic Theme aims to attract tourists to stay at this Elderly Friendly Resort Facility by focuses on comfort and natural atmosphere with a tropical building that takes the form of a traditional Balinese building.